Polysubstituted ferrocenes as tunable redox mediators - Waniek, Sven D.; Klett, Jan; Förster, Christoph; Heinze, Katja (Beilstein Journal of Organic Chemistry, 2018)
A series of four ferrocenyl ester compounds, 1-methoxycarbonyl- (1), 1,1’-bis(methoxycarbonyl)- (2), 1,1’,3-tris(methoxycarbonyl)- (3) and 1,1’,3,3’-tetrakis(methoxycarbonyl)ferrocene (4), has been studied with respect to their potential use as redox mediators. The impact of the number and position of ester groups present in 1–4 on the electrochemical potential E1/2 is correlated with the sum of Hammett constants. The 1/1+–4/4+ redox couples are chemically stable under the conditions of electrolysis as demonstrated by IR and UV–vis spectroelectrochemical methods. The energies of the C=O stretching vibrations of the ester moieties and the energies of the UV–vis absorptions of 1–4 and 1+–4+ correlate with the number of ester groups. Paramagnetic 1H NMR redox titration experiments give access to the chemical shifts of 1+–4+ and underline the fast electron self-exchange of the ferrocene/ferrocenium redox couples, required for rapid redox mediation in organic electrosynthesis.
Keywords: cyclic voltammetry; ferrocene; paramagnetic NMR spectroscopy; redox mediator; spectroelectrochemistry